1993
DOI: 10.1002/app.1993.070480308
|View full text |Cite
|
Sign up to set email alerts
|

Properties of hydroxypropyl methylcellulose–polyvinyl alcohol water systems, dispersants in vinyl chloride suspension polymerization

Abstract: SYNOPSISAqueous solutions of partly hydrolyzed polyvinyl acetate (polyvinyl alcohol, PVA) and hydroxypropyl methylcellulose (HPMC) are used together as dispersants in vinyl chloride suspension polymerization. Surface tension, viscosity, and cloud point ( C P ) of diluted PVA and HPMC solutions at room temperature, viscosity of concentrated solutions as a function of temperature, and incipient gelation temperatures ( IGT) were determined. Viscosity measurements show synergism of binary polymer mixtures. The syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…(Hydroxypropyl)methylcellulose (HPMC) is also used commonly as a suspension stabilizer (Cheng and Langsam, 1984;Chung and Wasan, 1988;Zilberman et al, 1993). Cheng and Langsam (1984) found that the particle structure of poly(vinyl chloride) produced by suspension polymerization using HPMC as stabilizer is controlled by the substitution and molecular weight of HPMC, while the molecular weight distribution shows no apparent effect.…”
Section: Effects Of Rheologicalmentioning
confidence: 99%
See 1 more Smart Citation
“…(Hydroxypropyl)methylcellulose (HPMC) is also used commonly as a suspension stabilizer (Cheng and Langsam, 1984;Chung and Wasan, 1988;Zilberman et al, 1993). Cheng and Langsam (1984) found that the particle structure of poly(vinyl chloride) produced by suspension polymerization using HPMC as stabilizer is controlled by the substitution and molecular weight of HPMC, while the molecular weight distribution shows no apparent effect.…”
Section: Effects Of Rheologicalmentioning
confidence: 99%
“…It is also known that the PVC particle properties greatly depend on the ratio between the components of the dispersing system, and the ability of the system is not an additive function of the ones related to PVA and HPMC alone. HPMC makes it possible to regulate the viscosity of the aqueous solutions, and PVA, if necessary, secures low interfacial tension (Zilberman et al, 1993). Macho et al (1994) modified PVA to different degrees by acetalization reactions with different aldehydes in the presence of hydrochloric acid as "catalyst".…”
Section: Effects Of Rheologicalmentioning
confidence: 99%
“…The incorporation of the Eudragit L100 nanoparticles in the methylcellulose hydrogels resulted in an increase in hydrogel spreadability, as shown in Figure 9a, and the corresponding spreadability factors are 9.09 mm 2 /g and 8.91 mm 2 /g for the NP-MC and Bud-NP-MC samples, respectively. Since Zilberman et al reported a decrease in surface tension for the mixtures of cellulose derivatives and PVA [67], we suggest that the presence of PVA in nanoparticle dispersion may contribute to the larger spreadability of the hydrogels containing the nanoparticles. The results from the spreadability test for the plain and nanoparticles containing hydrogels are presented in Figure 9.…”
Section: Samplementioning
confidence: 66%
“…At a higher use level of HPMC, the greater degree of entanglement of the linear polymer chains results in "virtual crosslinking," leading to the formation of a more robust gel layer [18]. HPMC is a versatile polymer for the production of tablets and is widely accepted as a pharmaceutical excipient for oral administration [19,20]. HPMC can be used to control the release behavior of hydrophilic and hydrophobic drugs through swelling, diffusion, and erosion processes [21].…”
Section: Introductionmentioning
confidence: 99%